Integrated Sensor System for Rice Conditions Monitoring Based UGV - Pei, Wang; Lan, Yubin; Xiwen, Luo; Zhiyan, Zhou; Wang, Zhigang (International Journal of Agricultural and Biological Engineering, 2014)
Ground-based platform systems provide a good tool for monitoring and managing crop conditions in precision agriculture applications and have been widely used for monitoring crop conditions. To develop an unmanned ground vehicle system (UGVS) based multi-sensors and test the feasibility of this system for monitoring rice conditions, an UGVS was developed to collect real-time rice condition information including NDVI values, reflectance measurements and crop canopy temperature in this study. Major components of the integrated system are GreenSeeker R100 system, hyper-spectroradiometer and infrared temperature sensor. The leaf area index (LAI) was measured by the CGMD302 Spectrometer. The Independent Samples T-Test method and the one way ANOVA method were used to determine the best spectral indices and analyze the relationship between the vegetation indices and rice LAI. It was found that the two best spectral indices for estimating LAI were NDVI (860 nm and 750 nm) with the correlation coefficient (R2) at 0.745 and RVI (853 nm and 751 nm) with the R2 at 0.724. The results show the UGVS can support multi-source information acquisition and is useful for crop management and precision agriculture applications. Keywords: unmanned ground vehicle system (UGVS), multi-sensors, rice growth condition, spectral vegetation indices, leaf area index (LAI) DOI: 10.3965/j.ijabe.20140702.009 Citation: Wang P, Lan Y B, Luo X W, Zhou Z Y, Wang Z, Wang Y. Integrated sensor system for monitoring rice growth conditions based on unmanned ground vehicle system. Int J Agric & Biol Eng, 2014; 7(2): 75－81.